2003
DOI: 10.1152/jn.00854.2002
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Depresses Excitatory Synaptic Transmission in the Nucleus Accumbens Through Dopaminergic and Purinergic Mechanisms

Abstract: Substance P (SP) is an undecapeptide that is co-localized with conventional transmitters in the nucleus accumbens (NAc). Its neurochemical and behavioral effects resemble those of cocaine and amphetamine. How SP accomplishes these effects is not known, partly because its cellular and synaptic effects are not well characterized. Using whole cell and nystatin-perforated patch recording in rat forebrain slices, we show here that SP, an excitatory neuropeptide, depresses evoked excitatory postsynaptic currents (EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 71 publications
(26 reference statements)
9
37
0
Order By: Relevance
“…In this regard, 17β‐estradiol is not the only neuromodulator that causes excitatory synaptic inhibition while increasing excitability. Other neuromodulators such as cholecystokinin have been shown to depress excitatory synaptic transmission that is preceded by depolarization of neurons leading to increased action potential firing (Kombian et al,2003). As mentioned previously, 17β‐estradiol may influence postsynaptic membrane responsiveness to various electrical and chemical stimuli by modulating several structures or mechanisms including ion channels, receptors and receptor‐mediated intracellular signalling.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, 17β‐estradiol is not the only neuromodulator that causes excitatory synaptic inhibition while increasing excitability. Other neuromodulators such as cholecystokinin have been shown to depress excitatory synaptic transmission that is preceded by depolarization of neurons leading to increased action potential firing (Kombian et al,2003). As mentioned previously, 17β‐estradiol may influence postsynaptic membrane responsiveness to various electrical and chemical stimuli by modulating several structures or mechanisms including ion channels, receptors and receptor‐mediated intracellular signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the affect of LiCl in increasing PPTA may seem counterproductive to the role of lithium in treating affective disorders, in which an increase in an excitatory neuropeptide may not seem beneficial; however, SP is also known to modulate the monoaminergic neurotransmitter systems that act to decrease cell excitability and that are major therapeutic targets for bipolar disorder, depression and addition (Santarelli et al 2001;Kombian et al 2003;Guiard et al 2007;Haddjeri and Blier 2008). Thus, the end result of lithium-mediated increases in SP could be excitatory or inhibitory depending on the neural networks on which SP is acting.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, morphological studies indicated that lesion of the nigrostriatal pathway increased the expression of substance P immunoreactivity in numerous pallidal cell bodies (Martorana et al, 2003), which may reflect a compensatory mechanism. However, since other basal ganglia nuclei (including striatum, entopeduncular nucleus) also express substance P receptors (Arai and Emson, 1986; Jakab and Goldman-Rakic, 1996; Mounir and Parent, 2002; Chen et al, 2003), and show electrophysiological response to substance P (Aosaki and Kawaguchi, 1996; Galarraga et al, 1999; Kombian et al, 2003a,b), the therapeutic effects of substance P administration would depend on the interaction of its actions on these nuclei. Thus, more experiments and evidence are needed before we could fully understand the functions of substance P in the whole basal ganglia circuit in normal conditions and movement disorders.…”
Section: Discussionmentioning
confidence: 99%